Rwanda: Desk study of extension and advisory services - MacNairn, Ian; Davis, Kristin E. (United States Agency for International Development, 2020)
Rwanda is a unique African country with a unique history. Like many other sub-Saharan African countries, agriculture is the key livelihood for the majority of the nation’s people. Rwanda is also one of the most densely-populated countries in the world, and there are many challenges for rural agriculture: access to land, access and high cost of agricultural inputs, small average landholdings, soil erosion and an undercapitalized private sector. Despite these barriers, Rwanda’s agricultural sector has produced significant agricultural growth since the 1994 genocide, taking advantage of the many opportunities that the country’s agricultural sector has including good technical capacity in both the private and public sector, two to three cropping seasons per year, manageable access to urban markets for most areas, good governmental support for ICT and business, lower levels of corruption compared to its neighbors, and opportunities for export to other countries in the East African Community. However, poverty levels, while declining, are still high.